Column-averaged dry-air mole fractions of CO2, CH4 and CO recorded during an urban measurement campaign in Munich in August 2018 with five solar-tracking Fourier transform spectrometers (EM27/SUN) - Florian Dietrich; Jia Chen; Andreas Forstmaier; Xiao Bi; Björn Reger; Andreas Luther; Jared Matzke; Mohammad Ramezani; Frank Hase; André Butz (PANGAEA, 2023)
In August 2018, we deployed five solar-tracking Fourier transform spectrometers (EM27/SUN) in the urban area of Munich to measure the column-averaged dry-air mole fraction of the three gases carbon dioxide (CO2), methane (CH4), and carbon monoxide (CO). The setup is characterized by a central station and a station in each compass direction, spaced about 20 km apart, to measure the inflow and outflow of the gas concentrations under any wind conditions. With this setup, it is possible to determine urban greenhouse gas emissions when an appropriate atmospheric model is applied to these concentration data in conjunction with additional meteorological parameters such as wind.